Perancangan Sistem Informasi Absensi Karyawan Pada CV. Azzara Gemilang Menggunakan Metode Waterfall - Rizal Amri Khoirul Hakim Ritonga; Muhammad Irwan Padli Nasution (CV. Multi Kreasi Media, 2025)
This web-based employee attendance system was developed to optimize the efficiency and accuracy of attendance recording at CV Azzara Gemilang, which was previously done manually. The system was created using the PHP programming language and MySQL database, by implementing the Waterfall development model which includes the needs analysis, design, implementation, and testing stages. The results of its implementation show the system's ability to automate the attendance recording process, store data centrally, and produce fast and accurate reports. Testing with the Black Box Testing method confirms that all the key features are operating properly according to the user's needs.